RELASI INTELEKTUAL, JAWA ISLAM, BUGIS ISLAM, DAN TURKI UTSMANI (Tinjauan Atas Sistem Kalender dalam Serat Widya Pradana, Lontara Pananrang dan Ruzname Darendeli) - Musonnif, Ahmad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
General description of relations between the Ottoman Turkey and pre-colonial Indonesian Muslim, is a relation between the central and branch relations as well as those who give legitimacy and those who are given legitimacy. Ottoman Turkey is the center that gives legitimacy while the Indonesian Muslim is the party which is a legitimate branch. This made the Ottoman Turkey superior in any field and the Indonesian Muslim became inferior. As for relations between Javanese-Bugis Muslims, it appears that Javanese Muslims have more influence on Bugis Muslims because Javanese Islam came earlier than Bugis Islam. Regarding the issue of Islamic calendar, there is one case where the Sunan Giri Calendar with its Wind Cycle appeared earlier than the Ruzname Darendeli calendar from the Ottoman Turkey. Whereas the Bugis Calendar is more influenced by the Javanese Calendar and may also influence the Ottoman Turkey?s Hijri Calendar Keywords: Intelectual relations, Islam, Calendar Gambaran umum relasi antara Turki Utsmani dan Muslim Nusantara pra-kolonial, merupakan relasi antara relasi pusat dan cabang serta pihak yang memberi legitimasi dan pihak yang diberi legitimasi. Turki Utsmani adalah pusat yang memberi legitimasi sedangkan Muslim Nusantara adalah pihak yang merupakan cabang yang dilegitimasi. Hal ini menjadikan Turki Utsmani menjadi Superior di bidang apapun dan Muslim Nusantara menjadi Inferior. Adapun relasi antar Muslim Jawa-Bugis, tampak Muslim Jawa lebih berpengaruh pada Muslim Bugis sebab Islam Jawa lebih Dahulu dari Islam Bugis. Terkait persoalan kelender Islam, ada satu kasus dimana Kalender Sunan Giri dengan Siklus Windunya muncul lebih dahulu dibanding dengan kalender Ruzname Darendeli dari Turki Utsmani. Sedangkan Kalender Bugis lebih dipengaruhi Kalender Jawa dan dimungkinkan juga mempengaruhi Kalender Hijri Turki Utsmani. Kata kunci: Relasi Intelektual, Islam, Kalender